Isopeptide bond formation mediated by δ-selenolysine for chemical ubiquitination - Akiyama, Tatsunari; Tanaka, Yusuke; Okamoto, Ryo; Kajihara, Yasuhiro; Izumi, Masayuki (Frontiers in Chemistry, 2023)
Protein ubiquitination is involved in nearly all biological processes in Eukaryotes. To gain precise insights into the function of ubiquitination in these processes, researchers frequently employ ubiquitinated protein probes with well-defined structures. While chemical protein synthesis has afforded a variety of ubiquitinated protein probes, there remains a demand for efficient synthesis methods for complex probes, such as ubiquitinated glycoproteins and ubiquitinated cysteine-containing proteins. In this study, we introduce a new method to obtain ubiquitinated proteins through isopeptide bond formation mediated by δ-selenolysine residues. We synthesized δ-selenolysine derivatives in both L- and D-forms starting from DL-δ-hydroxy-DL-lysine, accomplished by substituting the δ-mesylate with KSeCN and by enzymatic optical resolution with L- and D-aminoacylase. We synthesized ubiquitin (46–76)-α-hydrazide with a δ-seleno-L-lysine residue at position 48, as well as ubiquitin (46–76)-α-thioester, using solid-phase peptide synthesis. Subsequently, the δ-selenolysine-mediated ligation of these peptides, followed by one-pot deselenization, provided the desired isopeptide-linked ubiquitin peptide. The new δ-selenolysine-mediated isopeptide bond formation offers an alternative method to obtain complex ubiquitin- and ubiquitin-like probes with multiple post-translational modifications. These probes hold promise for advancing our understanding of ubiquitin biology.